Epidemiology and Outcomes of Candidemia in a Referral Center in Tehran - Mohammadreza Salehi; Zahra Ghomi; Reza Mirshahi; Seyed Ali Dehghan Manshadi; Omid Rezahosseini (Babol University of Medical Sciences, 2019)
Background: Bloodstream infection with Candida, or candidemia, is the most common Candida systemic infection. In this study, we investigated the characteristics of patients with candidemia to provide appropriate perspectives on these patients and reduce the associated mortality and morbidity. Methods: In this cross-sectional study, all patients with at least one positive blood culture of Candida spp. were investigated from April 2015 to March 2016 in Imam Khomeini Hospital Complex, Tehran, Iran. Results: A total of 74 patients (44 men and 30 women), with the mean age of 53.15±17.89 years, were enrolled in this study. Non-albicans Candida species was responsible for candidemia in 67.6% (50.74). The mean therapy intervals were 7 and 5.6±1.5 days in patients who died and were discharged, respectively. The differences in frequencies of urinary catheter and mechanical ventilation were statistically significant among patients who died and survived (P<0.001). Among the discharged patients, antifungal therapy was administered to 30.8% (12.39). The mortality rate was 54.3% (19.35) in the medical ward, 5.7% (2.35) in the surgical ward, and 40% (14.35) in the intensive care unit (P=0.041). The treatment was significantly associated with lower mortality than those with no treatment (OR=0.150 [0.023-0.996], P=0.05). Conclusion: The number of candidemia cases caused by non-albicans Candida species is continuously increasing in our center. We demonstrated the epidemiologic characteristics of patients with candidemia and the significant effects of timely and appropriate treatment on their outcomes. Further studies are needed to illuminate more aspects of this healthcare problem